Water stress tolerance in beans cv. Pinto Saltillo modified with the vacuolar pyrophosphatase-1 gene of Arabidopsis thaliana - Hernández, David Cadena; Ariza, Roberto Gaxiola; Mora Avilés, María Alejandra (Revista Mexicana de Ciencias Agrícolas, 2019)
The Arabidopsis Vacuolar Pyrophosphatase-1 (avp1) gene, which encodes the enzyme H+ pyrophosphatase, improves drought and salinity tolerance and increases biomass and yield when overexpressed in transgenic plants. The purpose of this study was to analyze the phenological, physiological and agronomic characteristics of beans cv. Pinto Saltillo (PS) transformed with the 35Sprom:avp1 gene under conditions of extreme water stress. The experimental design consisted of a random distribution of 10 homozygous plants for each of the 9 PS-avp1 lines, as well as unmodified control plants. Irrigation was suspended in the phenological stage of 50% flowering and water stress started from 100% to 9% volumetric water content (CVA), over 10 days. The results showed that the drought intensity index (IIS) was 0.78. Even though the stomatal conductance and perspiration showed a rate of decrease similar to the non-transformed plants, the photosynthetic rate of all PS-avp1 lines was higher than the control plants under conditions of water stress. The increase in total biomass in some PS-avp1 lines did not correlate with a higher yield. Seven of the nine lines evaluated showed a higher yield (35%-96%) compared to non-transformed PS plants under stress conditions, indicating greater efficiency in the translocation of photoassimilates to the target organs (seeds).